Optimal outpatient training for resident physicians’ general medicine in-training examination score: a cross-sectional study - Taiju Miyagami; Yuji Nishizaki; Taro Shimizu; Yu Yamamoto; Kiyoshi Shikino; Koshi Kataoka; Masanori Nojima; Gautam Deshpande; Toshio Naito; Yasuharu Tokuda (BMC Medical Education)
Abstract Background Outpatient training for resident physicians has been attracting attention in recent years. However, to our knowledge, there have only been a few surveys on outpatient training, particularly in Japan. This study evaluates outpatient care among Japanese resident physicians by determining how the volume of outpatient encounters and length of outpatient training correlate with residents’ clinical competence. Methods This study utilised the results of the General Medicine In-Training Examination (GM-ITE; resident clinical competency assessment) for 2,554 post-graduate year 2 (PGY 2) resident physicians in Japan, as well as a self-reported questionnaire regarding their educational training environments conducted after the examination. We investigated whether GM-ITE scores correlated with daily outpatient volume and duration of outpatient training. Results Regarding outpatient volume, having 1–5 new patient encounters per day was significantly associated with higher GM-ITE scores by multilevel analysis [0 patients: average score 43.7, 1–5 patients: adjusted estimated coefficient (aEC) 1.99, 95% confidence interval (CI) 0.44 to 3.55, P = 0.01]. Regarding the duration of outpatient training, residents trained for one month had the highest GM-ITE scores (one month: average score 46.9; two months: aEC -1.44, 95% CI -2.29 to -0.60, P < 0.001; three months: aEC -1.44, 95% CI -2.22 to -0.65, P < 0.001). Conclusion Minimal daily new outpatient visits and one month of outpatient training effectively correlated with residents’ basic clinical competence. Trial registration This study was approved by the Ethics Committee of the Japan Institute for Advancement of Medical Education Program (JAMEP; No. 22–30) and retrospectively registered.